Strategi Penyajian Berita Bengkulu.Antaranews.Com dalam Menarik Minat Baca Generasi Muda - Sinaga, Anugrah; Gushevinalti; Sonde Martadereja (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of technology, information and communication (ICT) is in line with the current development of online media where online media now relies on social media such as news websites with the aim of attracting the younger generation. If you look at it, many young people are more interested in platforms such as Instagram, Facebook, Twitter and TikTok. For this reason, online media continues to compete with each other to create unique and interesting content to attract the reading interest of the younger generation. In this research, the author wants to know how Bengkulu.antaranews.com's news presentation strategy is to attract the reading interest of the younger generation. In the current era of globalization, the younger generation is more dominant in opening online news than other media, however, the challenge is that the younger generation does not really like news in the form of text or the old method but prefers news in the form of videos, graphic designs and attractive infographics. In this case the author uses Make Ward's theory. Meanwhile, the research method used is qualitative research methods using interview and case study methods. The results of this research show how the news presentation strategy is carried out by Bengkulu.antaranews.com to attract the reading interest of the younger generation by utilizing social media and using features in it, one of which is creating a poll feature on Instagram, live broadcasts, multimedia news and creating content according to readers' needs. In this research, the online media audience for Bengkulu.antaranews.com is still dominated by the younger generation. The strategy implemented by Bengkulu.antaranews.com to face competition is by continuing to use an inverted pyramid writing structure and prioritizing news accuracy.